2014
DOI: 10.1021/la500013c
|View full text |Cite
|
Sign up to set email alerts
|

Binding between DNA and Carbon Nanotubes Strongly Depends upon Sequence and Chirality

Abstract: Certain single-stranded DNA (ssDNA) sequences are known to recognize their partner single-walled carbon nanotube (CNT). Here, we report on activation energies for the removal of several ssDNA sequences from a few CNT species by a surfactant molecule. We find that DNA sequences systematically have higher activation energy on their CNT recognition partner than on non-partner species. For example, the DNA sequence (TAT)4 has much lower activation energy on the (9,1) CNT than on its partner (6,5) CNT, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 35 publications
5
72
0
Order By: Relevance
“…The ability of these sequences to exhibit stronger chirality dependence than the other recognition sequences tested could be caused by an increased sensitivity of binding strength on SWNT chirality. This phenomenon was previously reported for the sequences (TAT) 4 , (CCA) 10 and (TTA) 4 TT, where surfactant exchange experiments indicated that the difference in binding strength across various chiralities was much larger for (TAT) 4 than for the other sequences [34].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The ability of these sequences to exhibit stronger chirality dependence than the other recognition sequences tested could be caused by an increased sensitivity of binding strength on SWNT chirality. This phenomenon was previously reported for the sequences (TAT) 4 , (CCA) 10 and (TTA) 4 TT, where surfactant exchange experiments indicated that the difference in binding strength across various chiralities was much larger for (TAT) 4 than for the other sequences [34].…”
Section: Resultssupporting
confidence: 82%
“…Thus, the chirality dependence observed in this study can be explained by corona structure variability-and hence, variability in analyte accessibility to the SWNT surface-across different chiralities for the same ssDNA wrapping. Molecular dynamics simulations have been extensively used to study the corona architecture of DNA-SWNT hybrids and a combination of molecular dynamics and surfactant exchange experiments have shown that corona architecture and binding strength vary across different chiralities for several sequences exhibiting separation capability including (TAT) 4 [32][33][34]. Both corona structure and binding strength are dependent on a combination of nanotube diameter and electronic properties, which can be clearly observed in the chirality dependent responses of (TAT) 4 -wrapped SWNTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 SWCNT have been used for the development of nanocomposite materials, 2 molecular detection agents, 3 molecular delivery vehicles, 4 electrochemical sensors, 5,6 optical sensors, 711 biologically compatible nanoconjugates, 12,13 and nanotube partitioning. 1419 Many SWCNT applications rely on their noncovalent functionalization with physisorbed polymers, such that the sp2 hybridization of the honeycomb carbon lattice of the SWCNT surface remains intact and fluorescent. Adsorbed polymers create a molecular corona around the SWCNT, which can facilitate the incorporation of SWCNT into bulk materials, 20 make SWCNT water-soluble and biocompatible, 21 appropriate for targeted delivery into organelles, 7 or enable SWCNT-based sensing.…”
Section: Introductionmentioning
confidence: 99%